Determining the Priority of Sharia Pension Fund Problems - Ardiansyah, Faisal; Wiyoko, Fathan (Islamic Economics Methodology, 2025)
The development of sharia pension funds in Indonesia still faces various structural, institutional, and social obstacles, despite the large potential of the national sharia financial market. This study aims to identify and determine the main priorities of the problem of sharia pension funds in Indonesia based on the perception of experts. The method used is the Delphi method involving five experts from academics, practitioners, and Islamic economic regulators. The analysis was carried out using three main indicators of the Delphi method, namely mean value, standard deviation, and interquartile range (IR) to measure the level of consensus. The results of the study showed that all 17 variables of the problem of sharia pension funds reached an adequate consensus level. The three main priority problems agreed upon by the experts are: (1) approval from the founder, (2) the lack of sharia principle guidelines for sharia pension funds, and (3) the limited qualifications of human resources in the implementation of sharia contracts. These findings confirm that the main obstacles to sharia pension funds are not only technical, but also institutional and governance, thus requiring comprehensive policy interventions from regulators and relevant stakeholders.